Oxytocin and Migraine Headache. (9th May 2017) - Tzabazis, Alexander; Kori, Shashi; Mechanic, Jordan; Miller, James; Pascual, Conrado; Manering, Neil; Carson, Dean; Klukinov, Michael; Spierings, Egilius; Jacobs, Daniel; Cuellar, Jason; Frey, William H.; et al.
Abstract : This article reviews material presented at the 2016 Scottsdale Headache Symposium. This presentation provided scientific results and rationale for the use of intranasal oxytocin for the treatment of migraine headache. Results from preclinical experiments are reviewed, including in vitro experiments demonstrating that trigeminal ganglia neurons possess oxytocin receptors and are inhibited by oxytocin. Furthermore, most of these same neurons contain CGRP, the release of which is inhibited by oxytocin. Results are also presented which demonstrate that nasal oxytocin inhibits responses of trigeminal nucleus caudalis neurons to noxious stimulation using either noxious facial shock or nitroglycerin infusion. These studies led to testing the analgesic effect of intranasal oxytocin in episodic migraineurs—studies which did not meet their primary endpoint of pain relief at 2 h, but which were highly informative and led to additional rat studies wherein inflammation was found to dramatically upregulate the number of oxytocin receptors available on trigeminal neurons. This importance of inflammation was supported by a series of in vivo rat behavioral studies, which demonstrated a clear craniofacial analgesic effect when a pre‐existing inflammatory injury was present. The significance of inflammation was further solidified by a small single‐dose clinical study, which showed analgesic efficacy that was substantially stronger in chronic migraine patients that had not taken an anti‐inflammatory drug within 24 h of oxytocin dosing. A follow‐on open label study examining effects of one month of intranasal oxytocin dosing did show a reduction in pain, but a more impressive decrease in the frequency of headaches in both chronic and high frequency episodic migraineurs. This study led to a multicountry double blind, placebo controlled study studying whether, over 2 months of dosing, "as needed" dosing of intranasal oxytocin by chronic and high frequency migraineurs would reduce the frequency of their headaches compared to a 1‐month baseline period. This study failed to meet its primary endpoint, due to an extraordinarily high placebo rate in the country of most of the patients (Chile), but was also highly informative, showing strong results in other countries and strong post hoc indications of efficacy. The results provide a strong argument for further development of intranasal oxytocin for migraine prophylaxis.